THE EFFECT OF CONSUMPTION OF YOUNG COCONUT (COCOS NUCIFERA L) ON CHOLESTEROL LEVELS IN HEALTHY PEOPLE - Aris Prasetyo; Alif Kufari; Septa Surya Wahyudi; Jauhar Firdaus; Adelia Handoko; Kristianingrum Dian Sofiana; Pipiet Wulandari (UNEJ e-Proceeding, 2022)
High blood cholesterol levels are risk factors that cause an increase in Low Density Lipoprotein (LDL) that it can form clots and plaque in the vascular which will result in the formation of atherosclerosis. Galactomannan is a natural ingredient that can reduce blood cholesterol levels by inhibiting its absorption and forming hydrogen bonds with cholesterol. In Indonesia, a potential source of galactomannan is coconut (Cocos Nucifera L). This study aims to determine the effect of consumption of young coconuts on cholesterol levels in healthy people. This research is an experimental clinical trial study with a pretest-posttest design. The sample of this study was twenty healthy people aged 18-25 years consisting of 10 men and 10 women. The treatment is in the form of consumption of coconut with 250 gram coconut meat and 150 mL coconut water with administration once a day for 14 days. The beginning and the end of the treatment blood cholesterol level were examined. after the treatment of coconut, consumption obtained a decrease in blood cholesterol levels by 17 participants and 3 participants with an increase in blood cholesterol levels. it can be concluded that there is a significant influence on the consumption of young coconuts to reduce blood cholesterol levels in healthy people. Keywords: cholesterol, coconut, galactomanan